2012
DOI: 10.1007/s10120-012-0166-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy of gastric cancer using LIGHT-secreting human umbilical cord blood-derived mesenchymal stem cells

Abstract: Background Mesenchymal stem cells (MSCs) have the ability to migrate into tumors and therefore are potential vehicles for the therapy of malignant diseases. In this study, we investigated the use of umbilical cord blood mesenchymal stem cells (UCB-MSCs) as carriers for a constant source of transgenic LIGHT (TNFSF14) to target tumor cells in vivo.Methods Lentiviral vectors carrying LIGHT genes were constructed, producing viral particles with a titer of 2 9 10 8 TU/L. Fourteen days after UCB-MSCs transfected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the gastric mucosa, quiescent and active stem cells have been reported, which suggests that there is dire need to design drugs that specifically target CSCs, including stem cell–targeting drugs, stemness-inhibitor drugs, stemness-promoting drugs, and microenvironment-modulating drugs [23, 62, 7476, 147]. For targeting GCSCs, several novel strategies have been suggested, including a combination of chemotherapy-associated apoptosis, targeted imaging, and tumor stem cell differentiation induction; inducing apoptosis in the tumor; therapies targeting GCSC cell surface molecules; monoclonal antibody development; targeting the GCSC microenvironment; and inhibiting GCSC pathways [77,81,93,118,122,142,148160]. Jiang et al [91] treated gastric tumor cells, which express CD90, with trastuzumab (humanized anti-ERBB2 antibody) and found that trastuzumab can reduce the CD90+ population in tumor size and growth when it is combined with traditional chemotherapy.…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the gastric mucosa, quiescent and active stem cells have been reported, which suggests that there is dire need to design drugs that specifically target CSCs, including stem cell–targeting drugs, stemness-inhibitor drugs, stemness-promoting drugs, and microenvironment-modulating drugs [23, 62, 7476, 147]. For targeting GCSCs, several novel strategies have been suggested, including a combination of chemotherapy-associated apoptosis, targeted imaging, and tumor stem cell differentiation induction; inducing apoptosis in the tumor; therapies targeting GCSC cell surface molecules; monoclonal antibody development; targeting the GCSC microenvironment; and inhibiting GCSC pathways [77,81,93,118,122,142,148160]. Jiang et al [91] treated gastric tumor cells, which express CD90, with trastuzumab (humanized anti-ERBB2 antibody) and found that trastuzumab can reduce the CD90+ population in tumor size and growth when it is combined with traditional chemotherapy.…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 99%
“…It is known that MSCs have the capacity to migrate into tumors; therefore, they can be utilized as potential vehicles cancer therapy. Zhu et al [160] engineered umblical cord blood mesenchymal stem cells (UCB-MSCs) to deliver a secretable form of LIGHT, a member of tumor necrosis factor (TNF) superfamily. They found that MSC-LIGHT had a strong suppressive effect on gastric cancer growth, which suggest that this system have the potential to be used as efficient delivery vehicles in the treatment of GCs Zhu et al [160].…”
Section: Gastric Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LIGHT expressing MSCs homed effectively to tumors and organized a potent anti-tumor immune therapy by stimulating an influx of T cells. In another study umbilical cord blood derived MSCs were engineered to express a secretable form of LIGHT and attenuated subcutaneous tumors in a model of human gastric cancer [39].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are of particular interest to stem cell‐based therapies for neuroregeneration not only due to their intrinsic neuronal potential and ability to differentiate into neural cell phenotypes both in vitro and in vivo (Tropel et al, ; Alexanian et al, ; Bae et al, ), but also because of their migration to sites of injury after intravenous infusion, and their ability to promote recovery of damaged tissues through secretion of a variety of cytokines and chemokines (Crigler et al, ; Pisati et al, ). Several studies reveal that implanted MSCs could incorporate into the injured spinal cord and display a tendency to migrate toward pathological insults which raises the hope for developing new therapeutic strategies for CNS injury repair (Shyu et al, ; Zhu et al, ). Furthermore, in case of injury, MSCs inhibit fibrotic remodeling and apoptosis, stimulate endogenous stem cell recruitment and proliferation, and reduce immune responses (Uccelli et al, ; Oh et al, ).…”
mentioning
confidence: 99%